Gendered touch women, men, and knowledge-making in early modern Europe - Antonelli, Francesca; Romano, Antonella 1962-; Savoia, Paolo 1980- (Nuncius series, 2022)
"This book aims at exploring how practical expertise, textual learning, and the gendered bodies intersected with the production of knowledge in early modern Europe. Gendered touch looks at both how representations of gendered bodies contributed to the production of knowledge, and at how practice itself was gendered. By exploring new archival material and by reading anew printed sources, the book inquiries about how knowledge was produced, translated, appropriated, and transmitted among different kinds of actors - both women and men - such as craftspeople, physicians, alchemists, apothecaries, music theorists, natural philosophers, and natural historians"--